Finance and Development, September 1979. (Finance and Development; Finance and Development, 1979)
This paper reviews the speech delivered by Mr. Robert S. McNamara, President of the World Bank in Geneva in an address to the Economic and Social Council of the United Nations on July 23, 1979. In McNamara's opinion, the 'massive disparities' of living standards in the world are likely to continue. For his address, Mr. McNamara drew on projections and analyses from the World Development Report, 1979, of the World Bank. Mr. McNamara also emphasized the interdependence of the developed and developing countries.